Reducing Nausea in Early Pregnancy with Lavender Aromatherapy: A Case Study Approach - Sri Martini; Marta Pastari; Suprida Suprida; Rohaya Rohaya; Jamila Jamila (Indonesian Journal of Global Health Research, 2024)
Emesis gravidarum (EG) is a common complaint of first-trimester pregnancy. EG shows nausea accompanied by vomiting, which usually occurs in the morning. EG can cause decreased appetite, vomiting, up to weight loss, risk of dehydration, and electrolyte imbalance. The psychology of pregnant women with EG will also be disturbed because of nausea and vomiting experienced. That's why EG events must be taken seriously. Limitations of the use of drugs during pregnancy must be considered. Alternative therapies such as lavender aromatherapy can be an alternative non-pharmacological therapy for pregnant women in the first trimester. Lavender aromatherapy can produce a strong refreshing Fragrance, affecting the hypothalamus's nerves to reduce nausea and vomiting. Research objective: to determine the application of lavender aromatherapy to reduce nausea intensity in first-trimester pregnant women in the Simpang Periuk Health Center Working Area, Lubuklinggau City, in 2024. Research Methods: This research is descriptive research with a case study approach. This study was conducted from April 18 to April 23, 2024. The subjects of this study were 2 pregnant women in the first-trimester with nausea category of mild to moderate nausea and vomiting, with measurement of the nausea scale before and after the intervention, using the Pregnancy Unique Quantification Of Emesis assessment. (PUQE). Both subjects were given 3-5 drops of lavender aromatherapy, using a diffuser, inhaled for 5-30 minutes for three days in the intervention. Results: after giving lavender aromatherapy therapy, both subjects showed a decrease in the PUQE score, from moderate to mild nausea and vomiting. Conclusion: Interventation lavender aromatherapy effectively reduces nausea in first-trimester pregnant women, with several influencing factors including; pregnancy history, parity, occupation, and age.